Evaluation Of COVID Drugs Management in Pharmaceutical Installations Of Royal Prima Hospital Medan During the COVID-19 Pandemic - Dicca Brentazzoly Br Tarigan; Chrismis N. Ginting; Sri Lestari Ramadhani Nasution (Journal Research of Social Science, Economics, and Management, 2022)
Coronavirus Disease 2019 (COVID-19) has been declared by WHO as a global pandemic and in Indonesia it is declared as a type of disease that causes public health emergencies and non-natural disasters, which is not only causing death but also cause significant economic losses, so it is necessary to take steps to overcome it including prevention and control. This study aimed to analyze the evaluation of the handling of Covid drugs at the Pharmacy Installation of the Royal Prima Hospital in Medan during the COVID-19 Pandemic. This study used qualitative research located at the Pharmacy Installation of RSU Royal Prima Medan during the COVID-19 Pandemic. While The population in this study were 5 informants consisting of the Director of Medical Services, Head of Pharmacy Installation at Royal Prima Hospital Medan, Head of Pharmacy Warehouse, Pharmacist, and Assistant Pharmacist. In this study, the techniques used in data collection methods were Direct Observation, In-Depth Interviews, and Document Literature. The data analysis method was carried out by compiling, discussing, and evaluating the data and the results of interviews/observations using the Triangulation Test. Based on results studies, this state has carried out the process of procurement, receipt, storage, and distribution in the evaluation management drug covid on installation Pharmacy at Hospital Royal Prima Medan during the COVID-19 pandemic with supported with existence existing facilities and infrastructure and the number of available human resources at Hospital Royal Prima Medan.